2021
DOI: 10.1007/s12182-021-00548-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of flue gas water-alternating gas (flue gas–WAG) injection for enhanced oil recovery and multicomponent flue gas storage in the post-waterflooding reservoir

Abstract: Flue gas flooding is one of the important technologies to improve oil recovery and achieve greenhouse gas storage. In order to study multicomponent flue gas storage capacity and enhanced oil recovery (EOR) performance of flue gas water-alternating gas (flue gas–WAG) injection after continuous waterflooding in an oil reservoir, a long core flooding system was built. The experimental results showed that the oil recovery factor of flue gas–WAG flooding was increased by 21.25% after continuous waterflooding and fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…However, understanding how to properly treat the flue gas generated from combustion has become a major problem. As is known, flue gas flooding has been an environment-friendly and effective EOR method in many oilfields [ 1 , 2 ]. Hence, it is considered to be a promising method to improve the oil displacement efficiency in the HONG reservoir of the Xinjiang oilfield, with a low matrix permeability of 58 mD, a porosity of 17.8%, and a low reservoir temperature of 42 °C.…”
Section: Introductionmentioning
confidence: 99%
“…However, understanding how to properly treat the flue gas generated from combustion has become a major problem. As is known, flue gas flooding has been an environment-friendly and effective EOR method in many oilfields [ 1 , 2 ]. Hence, it is considered to be a promising method to improve the oil displacement efficiency in the HONG reservoir of the Xinjiang oilfield, with a low matrix permeability of 58 mD, a porosity of 17.8%, and a low reservoir temperature of 42 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Alagorni et al claimed that when water alternating gas (WAG-N 2 ) was used, recovery was widely improved owing to the combination of gas and water and the improvement in microscopic displacement achieved by reducing viscous fingering and density dislocation, as well as sweeping the unswept area. Wang et al found that the oil recovery rate reached 69.52% when the WAG-flue gas was applied to the reservoir after water flooding.…”
Section: Literature Review and Discussion On Different Oil Displaceme...mentioning
confidence: 99%
“…The efficiency of water-alternating-gas injection technology has been documented in many papers [3,[12][13][14][15][16]. A number of studies [10-11, [17][18][19] have shown that this technology can be used with exhaust gas with higher efficiency compared to other technologies.…”
Section: Discussionmentioning
confidence: 99%